EFFICIENT IMAGE RETRIEVAL THROUGH HYBRID FEATURE SET AND NEURAL NETWORK - Arora, Nitin; Ashok, Alaknanda; Tiwari, Shamik (APTIKOM Journal on Computer Science and Information Technologies, 2018)
Images are an important part of daily life. The huge repository of digitally existing images cannot be easilycontrolled by any individual. Extensive scanning of the image database is very much essential to search a particularimage from the huge repository. In some cases, this procedure becomes very exhaustive also. As a result, if a count often thousand, lakhs or considerably more images are included in image database, then it may be transformed into atedious and never ending process. Content-based image retrieval (CBIR) is a technique, which is used for retrievingany image. This type of image retrieval procedure is centred on the actual content of image. This paper proposed amodel of hybrid feature set of Haar wavelets and Gabor features and analysed with different existing models imageretrieval. Content based image retrieval using hybrid feature set of Haar wavelets and Gabor features superiors onother models.